2021
DOI: 10.3390/ijms22105205
|View full text |Cite
|
Sign up to set email alerts
|

A MADS-Box Gene CiMADS43 Is Involved in Citrus Flowering and Leaf Development through Interaction with CiAGL9

Abstract: MADS-box genes are involved in various developmental processes including vegetative development, flower architecture, flowering, pollen formation, seed and fruit development. However, the function of most MADS-box genes and their regulation mechanism are still unclear in woody plants compared with model plants. In this study, a MADS-box gene (CiMADS43) was identified in citrus. Phylogenetic and sequence analysis showed that CiMADS43 is a GOA-like Bsister MADS-box gene. It was localized in the nucleus and as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 81 publications
(115 reference statements)
0
25
0
Order By: Relevance
“…It is strange that the VIGS phenotype of CiKN6 is similar to its overexpression. This phenomenon may be mainly due to feedback regulation caused by gene function redundancy, and it has been reported in the development of citrus leaves (Ye et al., 2021). Furthermore, these results also suggested that CiKN1 and CiKN6 may cooperate to regulate the development of citrus leaf shape, and CiKN6 plays a more important role based on the VIGS analysis.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…It is strange that the VIGS phenotype of CiKN6 is similar to its overexpression. This phenomenon may be mainly due to feedback regulation caused by gene function redundancy, and it has been reported in the development of citrus leaves (Ye et al., 2021). Furthermore, these results also suggested that CiKN1 and CiKN6 may cooperate to regulate the development of citrus leaf shape, and CiKN6 plays a more important role based on the VIGS analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Arabidopsis was transformed by the floral‐dip method (Clough & Bent, 1998). Agrobacterium ‐mediated lemon transformation of stem segments was performed as previously described (Fu et al., 2011; Ye et al., 2021). The positive plants were detected by PCR amplification of genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The LEAFY and UFO genes have a similar function in conifers; the LEAFY gene interacts with the UFO gene by cloning and yeast two-hybrid techniques, and it is speculated that the UFO gene in Metasequoia glyptostroboides may act as a transcriptional cofactor to regulate the LEAFY gene activity and, thus, participate in the regulation of the flower meristem development [55]. MADS-box genes, a class of important transcriptional regulatory factors in eukaryotes (animals, plants and fungi), play an important role in growth and development regulation and signal transduction [56,57]. There are studies that show that three MADS-box genes (PrMADS1, PrMADS2 and PrMADS3), LEAFY/FLORICAULA and NEEDLY (NLY) were highly participated in the early stages of initiation and differentiation of P. radiata male and female cone buds, as well as vegetative buds [58].…”
Section: Molecular Mechanismsmentioning
confidence: 99%